2012
DOI: 10.1093/bioinformatics/bts698
|View full text |Cite
|
Sign up to set email alerts
|

SM2miR: a database of the experimentally validated small molecules’ effects on microRNA expression

Abstract: SM2miR is freely available at http://bioinfo.hrbmu.edu.cn/SM2miR/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 17 publications
2
147
0
1
Order By: Relevance
“…For example, three other drugs, irbesartan, pseudoephedrine and vinblastine, can target JUN (Figure 6), indicating that the three drugs may affect the pan-cancer FFL JUN_hsa-miR-21-5p_MSH2 through mediating their drug target JUN as the mechanism of ATO. In addition, we obtained the drugs that can affect miRNA expression from the SM2miR database, which collects the experimentally validated small molecule drug effects on miRNA expression [72]. We found that the expression of hsa-miR-195-5p, hsa-miR-34a-5p and hsa-miR-21-5p could be regulated by some other FDA-approved drugs, suggesting that they might have the anticancer activity through modulating the pan-cancer FFLs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, three other drugs, irbesartan, pseudoephedrine and vinblastine, can target JUN (Figure 6), indicating that the three drugs may affect the pan-cancer FFL JUN_hsa-miR-21-5p_MSH2 through mediating their drug target JUN as the mechanism of ATO. In addition, we obtained the drugs that can affect miRNA expression from the SM2miR database, which collects the experimentally validated small molecule drug effects on miRNA expression [72]. We found that the expression of hsa-miR-195-5p, hsa-miR-34a-5p and hsa-miR-21-5p could be regulated by some other FDA-approved drugs, suggesting that they might have the anticancer activity through modulating the pan-cancer FFLs.…”
Section: Resultsmentioning
confidence: 99%
“…Although chemical approaches are a very young field in stem cell research, these small molecules exhibit a similar biological outcome to that achieved with the use of miRNAs in stem cell fate regulation [35] . Recently, small molecules have been correlated with endogenous miRNA expression and function [197][198][199][200][201][202] . Therefore, identifying the relationship between miRNAs and small molecules could provide new insights for drug development for regenerative medicine and elucidate detailed mechanisms of miRNA expression and function in the control of stem cell fate.…”
Section: Small Molecules and Stem Cell Fatementioning
confidence: 99%
“…Along with the growth of miRNA transfection experiments, it is possible to regard the effects of the miRNA on gene expression at whole genome level, which more directly reflects alteration of gene expression affected by the perturbed miRNA. What's more, miREnvironment and SM2miR database have been constructed to collect the experimentally supported associations between small molecules and miRNAs [17, 18], Currently, miREnvironment database have collected complex interactions (3857 entries) among 1242 miRNAs, 305 phenotypes and 394 environment factors (including a few small molecules). SM2miR database have collected the 5160 records between 255 small molecules and 1680 miRNAs, and provided the effects (up-regulated and down-regulated) of small molecules on miRNA expression, and integrated all associations between drugs and miRNAs in miREnvironment database.…”
Section: Introductionmentioning
confidence: 99%